2005
DOI: 10.1002/mrd.20334
|View full text |Cite
|
Sign up to set email alerts
|

XY chromosomal bivalent: Nucleolar attraction

Abstract: Nucleolar organization by autosomal bivalents occurs during male meiotic prophase in mammalian species. During late leptotene-early zygotene stages, several autosomal bivalents are engaged in ribosomal RNA synthesis. At pachytene stage, nucleolar masses detach from the sites of primary autosomal origin, relocate close to the XY chromosomal pair, and nucleolar components become segregated. In early pachytene, an extensive synaptonemal complex at the pseudoautosomal region, links X and Y chromosomes in close jux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…J-L in Figure 1 show SCP3 expression in developing rat testes (positive control). Note SCP3 immunostaining of spermatogonial nucleoli in the 3-day-old rat (arrowhead, J), which is characteristic for early stages of meiotic prophase 13 and resembles observations in primordial follicle oocytes of postovulatory adult human and monkey ovaries (see Fig. 1F-H).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…J-L in Figure 1 show SCP3 expression in developing rat testes (positive control). Note SCP3 immunostaining of spermatogonial nucleoli in the 3-day-old rat (arrowhead, J), which is characteristic for early stages of meiotic prophase 13 and resembles observations in primordial follicle oocytes of postovulatory adult human and monkey ovaries (see Fig. 1F-H).…”
supporting
confidence: 64%
“…Recently, Tres reported that male germ cells exhibit nucleolar SCP3 expression during early stages of meiotic prophase. 13 In addition, an SCP3+ synapsis of two chromosomes was detected in human primordial follicle oocytes (arrowhead, H and insert), possibly representing XX chromosomal synapsis, since sex chromosomes start synapsis during early zygotene, before autosomes synapse. 13 Observations from twelve human cases studied are summarized in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the SCP3 immunostaining was observed in the nucleoli of oocytes in some primordial follicles in human (arrowhead, panel F) and monkey ovaries (white arrowhead, panel G). Tres reported that male germ cells exhibit nucleolar SCP3 expression during early stages of meiotic prophase (Tres, 2005). In addition, an SCP3 þ synapsis of two chromosomes was detected in human primordial follicle oocyte (arrowhead, panel H and insert), possibly representing XX chromosomal synapsis, since sex chromosomes start synapsis during early zygotene, before autosomes synapse (Tres, 2005).…”
Section: Localization Of Scp3 In Adult Human and Monkey Ovariesmentioning
confidence: 94%
“…Tres reported that male germ cells exhibit nucleolar SCP3 expression during early stages of meiotic prophase (Tres, 2005). In addition, an SCP3 þ synapsis of two chromosomes was detected in human primordial follicle oocyte (arrowhead, panel H and insert), possibly representing XX chromosomal synapsis, since sex chromosomes start synapsis during early zygotene, before autosomes synapse (Tres, 2005). Rare SCP3 þ oocytes (<10%) were detected in midfollicular phase ovaries.…”
Section: Localization Of Scp3 In Adult Human and Monkey Ovariesmentioning
confidence: 94%